LatHyS global hybrid simulation of the BepiColombo second Venus flyby. (1st September 2022) - Aizawa, S.; Persson, M.; Menez, T.; André, N.; Modolo, R.; Génot, V.; Sanchez-Cano, B.; Volwerk, M.; Chaufray, J.-Y.; Baskevitch, C.; Heyner, D.; Saito, Y.; et al.
Abstract: Plasma and magnetic field observations by BepiColombo during its 2nd Venus flyby in August 10, 2021 have been examined and compared with the newly developed global hybrid simulation LatHyS for the Venusian environment. The LatHyS-Venus simulation was first validated by a comparison with Venus Express observations obtained during average solar wind conditions, before it was applied to the BepiColombo flyby using as inputs solar wind parameters measured upstream of Venus by Solar Orbiter. The simulation confirms that BepiColombo passed through the stagnation region of Venus, which supports the results obtained by data analysis. In addition, we have sampled the plasma parameters along the BepiColombo trajectory and constructed the energy spectrum for two species, i.e., protons of both solar wind and planetary origins, and planetary oxygen ions, and discussed the possible effects due to the limited field of views of the plasma instruments onboard BepiColombo. The most intense observational features are properly captured in the LatHyS-Venus simulation, which show that the model is a powerful tool for interpreting and understanding in-situ data obtained from the instruments with a limited field of views. The estimated ion escape for protons and oxygen ions at Venus during the BepiColombo flyby is of the order of ∼ 10 24 ions/s, which is the same order of magnitude compared to the estimation from Venus Express observations at the solar minimum. Highlights: 1) We have developed the global hybrid simulation for the Venusian environment. 2) Observations by BepiColombo during its 2nd Venus flyby in August 10, 2021 have been examined. 3) The possible effects due to the limited field of views of the plasma instruments onboard BepiColombo have been discussed by sampling plasmas in the simulation domain.